Structure and conformation of photosynthetic pigments and related compounds. 15. Conformational analysis of chlorophyll derivatives - implications for hydroporphyrins in vivo - Gibbons, Daire; Flanagan, Keith J.; Pounot, Léa; Senge, Mathias O. (Photochemical & photobiological sciences, 2019)
Chlorophylls are fundamental macrocyclic cofactors in photosynthetic reaction centers and light-harvesting complexes. Their biological function is well understood on the basis of protein structural data and a significant body of information indicates that the conformation of tetrapyrroles plays a large role in controlling their biological activity. While there is no small molecule crystal structure of chlorophyll, the normal-coordinate structural decomposition (NSD) method is a very useful analytical tool for conformational analysis of chlorophylls, using tetrapyrroles that mimic their structure. NSD allows for an analysis of the individual macrocyclic distortion modes and their contributions to the overall conformation. Herein, we present our own validation of the NSD program and use it to carry out a conformational analysis of chlorophyll-related compounds. Metal insertions, peripheral substi-tuents, and solvents in the unit cell give rise to different NSD profiles in chlorophyll derivatives. These range from planar and non-planar conformations upon metal insertions, to polar peripheral substituents, and fused rings in chlorins. Substituent effects are clearly evidenced in highly β-substituted chlorins and while bacteriochlorins and isobacteriochlorins experience similar effects to the chlorins, they are also subject to solvent effects, causing the macrocycle to be non-planar. Overall, we report a first conformational analysis of all 'chlorophyll'-related small molecule crystal structures at an atomic level.